2020
DOI: 10.1111/jdv.16762
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features of subungual melanoma according to the extent of Hutchinson’s nail sign: a retrospective single‐centre study

Abstract: Background Hutchinson’s nail sign (HS) is among the diagnostic criteria for subungual melanoma (SUM). However, there is minimal evidence supporting the overall clinical significance of HS in SUM. Objectives To identify clinicopathological features of SUM according to the extent of HS. Methods Retrospective cohort study was performed with consecutive SUM patients at a single centre from January 2006 to December 2017. The extent of HS was defined by the number of affected nail folds (range 0–4). Comparison group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Sohng et al. demonstrated that the Hutchinson sign affecting over two nail folds was positively correlated with amputation or higher T stage 44 . Hyokyung et al.…”
Section: Discussionmentioning
confidence: 99%
“…Sohng et al. demonstrated that the Hutchinson sign affecting over two nail folds was positively correlated with amputation or higher T stage 44 . Hyokyung et al.…”
Section: Discussionmentioning
confidence: 99%
“…2,13 Also, a recent study has shown that the extent of HS is significantly associated with higher tumor stage of SUM. 14 Therefore, in invasive melanoma, HS is much more likely to be observed and the melanoma cells are more likely to be visible in a pathologic examination of HS, which in turn may result in a bias. Thus, we attempted to confirm our assumptions in the early stage of SUM.…”
Section: Discussionmentioning
confidence: 99%
“…The latter has been described as a periungual extension of pigment that may affect the nail folds and/or the hyponychium. This finding has been associated with an increased risk for advanced‐stage melanoma 5 …”
Section: Clinical Challengesmentioning
confidence: 97%